ANALYSIS OF PULP BLEACHING SEQUENCES IN THE RETENTION OF KAOLIN AND IN THE PROPERTIES OF PAPER - Santos, Ivan Rodrigues dos [UNESP]; Ventorim, Gustavo [UNESP]; Caraschi, Jose Claudio [UNESP]; Comelato Favaro, Jaqueline Silveira (Univ Federal Vicosa, 2015)
The aim of this study was to investigate the influence of different bleaching sequences at different amounts of kaolin in paper properties. To do that, three different ECF bleaching sequences were taken to the same O-2-delignified eucalyptus pulp, these being D (E + P) DP (reference ECF), AHTD (E + P) DP (A-ECF) and A(HT)D (E + P) P (ECF-Light), 20 kg/t o. d. hydrogen peroxide in the final stage. The pulps were submitted to bleaching to obtain 90 +/- 0.5% ISO brightness. After that, the replacement of the fiber by filler kaolin type in a proportion of 0% to 35% in increments of 5% were made for each pulp. The pulp sheets formed with a weight of 60 g/m(2) were characterized for physical and mechanical properties. Fiber dimensions obtained for each bleaching sequence were also analyzed. The results showed that the bleaching sequence influence on both the retention due the size of fibers and the fines content generated by each bleaching sequence as well as the paper physical and mechanical properties for each kaolin content. The ECF-Light sequence showed better retention and paper produced with the pulp showed a better smoothness, while sequence OAHT(E + P) DP showed higher internal resistance and higher compressive strength. The ECF pulp showed better results for tear index, higher viscosity and yield and fiber quality. It was concluded that the greater the amount of kaolin in paper, the lower its mechanical strength.
Keywords: Kaolin; Retention; Pulp Bleaching